2012
DOI: 10.1002/pssa.201228077
|View full text |Cite
|
Sign up to set email alerts
|

Optical and mechanical properties of transparent SrTiO3 thin films deposited by ECR ion beam sputter deposition

Abstract: SrTiO 3 (STO) thin films have been deposited on glass substrates by electron cyclotron resonance (ECR) ion beam sputter deposition at different substrate temperatures (100-600 8C). The structural characteristics of the deposited films show a transition from amorphous phase to polycrystalline phase at 600 8C. The films exhibit good transparency with an interference pattern in the visible region and a very smooth surface without cracks. The refractive index of the films increases with an increase of the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Finally, the reported hardness of materials reported in this study is in good agreement with the hardness reported for similar materials. [43][44][45][46][47][48][49][50] The fracture toughness of the conventionally sintered pristine materials does not have a systematic variation with regard to the grain size or the acceptor dopant level. It is…”
Section: (3) Hardness and Fracture Toughness Of Pristine Bzy-based Mamentioning
confidence: 99%
“…Finally, the reported hardness of materials reported in this study is in good agreement with the hardness reported for similar materials. [43][44][45][46][47][48][49][50] The fracture toughness of the conventionally sintered pristine materials does not have a systematic variation with regard to the grain size or the acceptor dopant level. It is…”
Section: (3) Hardness and Fracture Toughness Of Pristine Bzy-based Mamentioning
confidence: 99%
“…An increase of surface roughness after the annealing process might be explained by the formation of the cluster like nano-grains. Furthermore, nanocrystal grain boundaries might be responsible from the formation of grain-boundary grooves, which significantly contributes to a rougher film surface [25][26][27]. As mentioned in our previous study, rms roughness in STO films deposited at 0.40 Pa with 0% O 2 flow rate is lower than 0.2 nm [28].…”
Section: Resultsmentioning
confidence: 63%
“…Absorption coefficients were calculated from k(λ) values (α(λ) = 4πk(λ)/λ). The optical band gap energy (E g ) was evaluated using Tauc formula [25]. The direct and indirect band gaps were determined from (αhv) 2 and (αhv) 1/2 versus hv, plots, respectively.…”
Section: Film Characterizationmentioning
confidence: 99%
“…11,15,17 The optical band gaps of the pure SrTiO 3 and CQD/ SrTiO 3 nanocomposite can be estimated via the formula (ahn) n ¼ A(hn À E g ), where a, h, n, E g , and A are the absorption coef-cient, Planck constant, light frequency, band gap, and a constant, respectively, and n is an exponent determined by the nature of the electron transition during the absorption process (n ¼ 2 for allowed direct transition and n ¼ 1/2 for allowed indirect transition). 19,44,45 Fig. 5b shows a curve of (ahn) 2 versus hn from which the band gaps of SrTiO 3 and CQD/SrTiO 3 were estimated to be 3.16 and 3.15 eV, respectively.…”
Section: Optical Propertiesmentioning
confidence: 99%